POLIGAMI TIDAK TERCATAT DI INDONESIA: KAJIAN YURIDIS BERDASARKAN KOMPILASI HUKUM ISLAM - cahaya denisa, Norma; Nunung Radliyah; Sepriyadi Adhan; Kasmawati; Elly Nurlaili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the juridical implications of unregistered polygamous marriages in Indonesia based on the provisions of the Compilation of Islamic Law (KHI). Although such marriages may be religiously valid, the absence of official registration results in the marriage not being legally recognized by the state, creating significant legal vulnerabilities for both wives and children. This research employs a normative legal approach by analyzing statutory regulations, the KHI, and relevant court decisions. The findings indicate that KHI regulates polygamy through strict requirements, including court authorization, the husband’s ability to act fairly, and consent from the first wife. Failure to meet these requirements renders unregistered polygamy a violation of administrative order and without legal force. As a result, wives lose access to legal protection, while children face obstacles in establishing lineage and civil rights. This study emphasizes the importance of marriage registration as a foundation for legal protection.